Behavioral Finance of MSMEs: The Role of Digital Finance, Financial Literacy, and Financial Attitude - Maulani, Rury Indah; Risman, Asep (Universitas Mercu Buana, 2025)
This study aims to examine the influence of digital finance, financial literacy, and financial attitudes on the financial management behavior of Micro, Small, and Medium Enterprises (MSMEs) in the City of Tangerang. The population in this research consists of 115,000 MSME actors. The sample used comprises 100 respondents, determined based on the Slovin formula. The sampling technique employed is simple random sampling. Data were collected through a survey method using a questionnaire as the research instrument. The data were analyzed using the Partial Least Square (PLS) software. The findings demonstrate that digital finance has a positive effect on financial management behavior, financial literacy positively influences financial management behavior, and financial attitudes also have a positive impact on financial management behavior.